Impacto en la reducción del presupuesto del Gobierno Autónomo Descentralizado de la Parroquia Caracol en el periodo 2022- 2023. - León Aspiazu, Consuelo Marisol (2024)
In this investigation we will carry out an analysis on the reduction that the Decentralized Autonomous Government of La Parroquia Caracol has had in the budget in the Period 2022-2023, in which we identify the problem that has been presenting, thus allowing us to have a better perspective of the budget of the Rural GAD of the Caracol Parish, in addition to this we conducted an interview with Eng. Nayeli Alvarez Secretary-Treasurer of the Parish GAD, who provided us with the necessary information, to learn more about the reductions that have been presented in this GAD we carried out a horizontal analysis which allowed us to know the variations that were generated during the period 2022-2023, the main objective of this case study is to know the impact that the budget reduction had within the GAD and how this affected the community, in which we used the Analytical - quantitative methods helped us collect the data and know the results obtained, which will be carefully analyzed, and we will be able to have a better perspective of the current situation of the Decentralized Autonomous Government of La Parroquia Caracol; Finally, with all the information obtained, the institution will be able to make decisions that help them have better control of the budgets given the reduction they have presented.